Computational investigation of the selectivity of salen and tetrahydrosalen compounds towards the tumor-associated hCA XII isozyme. - Akdemir, ATİLLA; AKDEMİR, ATİLLA; SUPURAN, CT; De, Monte; CARRADORI, S (My University, 2015)
In previous work, 14 salen and tetrahydrosalen compounds have been synthesized and tested in enzyme inhibition assays against cytosolic human carbonic anhydrase isozymes I and II (hCA I and II) and tumor-associated isozymes IX and XII (hCA IX and XII). These compounds show selectivity against hCA XII over hCA I, II and IX. In this study, molecular modeling and docking studies were applied to understand this preference of the compounds for hCA XII. Most likely, the compounds can displace the zinc-bound water molecule of hCA XII to form a direct interaction with the Zn2+ ion. In the other isozymes, the compounds might not be able to displace the water molecule nor are they expected to interact with the Zn2+ ion.
Keywords: Carbonic anhydrase inhibitor